Writing about female oppression : the social and political significance of Tsitsi Dangarembga's Nervous conditions - Broekman, Shirley Jeanne (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.A.)--University of Stellenbosch, 1999.